The Effect of Gross Profit, Operating Profit and Net Profit on Future Cash Flow Prediction at the Company of Telecommunications Sub Sector on IDX in 2014-2019 - Leo Hutagalung; Harlyn Siagian (Ekonomis: Journal of Economics and Business, 2022)
This study was structured with the aim of knowing the effect of gross profit, operating profit and net profit on the prediction of future cash flows in telecommunications sub-sector companies listed on the Indonesian stock exchange. This research was conducted focused on the telecommunications sub-sector companies listed on the Indonesia Stock Exchange in 2014-2019. The sampling method used is purposive sampling. Through this sampling method, 5 companies were obtained that could be used as samples with a research period of 6 years. Therefore, in this study, the number of this study was 30 units of analysis. This study uses descriptive statistical analysis, correlation coefficient analysis, coefficient of determination analysis, simple regression analysis, and multiple regression analysis in analyzing all data. Testing the data used in this study is the partial t-significance test, the classical assumption test, and the F simulation test. From the research conducted, the results show that the gross profit and operating profit variables partially have no significant effect on future cash flows while the net income variable shows that partially significant effect on cash flows in the future. The variables of gross profit, operating profit and net profit simultaneously show a significant effect on future cash flows.